2022
DOI: 10.3390/cells11050792
|View full text |Cite
|
Sign up to set email alerts
|

Altered RBP1 Gene Expression Impacts Epithelial Cell Retinoic Acid, Proliferation, and Microenvironment

Abstract: Vitamin A is an essential diet-derived nutrient that has biological activity affected through an active metabolite, all-trans retinoic acid (atRA). Retinol-binding protein type 1 (RBP1) is an intracellular chaperone that binds retinol and retinal with high affinity, protects retinoids from non-specific oxidation, and delivers retinoids to specific enzymes to facilitate biosynthesis of RA. RBP1 expression is reduced in many of the most prevalent cancers, including breast cancer. Here, we sought to understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The chemokine CXCL1, vital in inflammatory diseases and tumors, shows that its increased presence in BC stroma is associated with higher tumor grade, disease recurrence, and lower patient survival 52 , 53 . RBP1, an intracellular carrier for retinol and retinaldehyde, is notably reduced in common cancers, including BC 54 . Interestingly, previous studies indicate that STC2 is involved in several malignant tumor processes and is upregulated in various cancers, leading to poorer outcomes 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine CXCL1, vital in inflammatory diseases and tumors, shows that its increased presence in BC stroma is associated with higher tumor grade, disease recurrence, and lower patient survival 52 , 53 . RBP1, an intracellular carrier for retinol and retinaldehyde, is notably reduced in common cancers, including BC 54 . Interestingly, previous studies indicate that STC2 is involved in several malignant tumor processes and is upregulated in various cancers, leading to poorer outcomes 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…RBP1 , an intracellular chaperone that binds retinol and retinal with high affinity, protects retinoids from non-specific oxidation and delivers retinoids to specific enzymes ( 49 ). Yu et al ( 50 ) found that altered RBP1 expression affects epithelial cell retinoic acid, proliferation, and microenvironment. However, its role in AF remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…RPB1 binds to retinol and prevents retinoids from being non‐specifically oxidized. RPB1 then transports the retinoids for further synthesis into retinoic acid (Yu et al., 2022). In PAX6 −/− mice RBP1 was found to be expressed at low levels (Holm et al., 2007).…”
Section: Discussionmentioning
confidence: 99%